Traduction et culture : enjeux de médiation dans un monde interconnecté Tradition and culture mediation: challenges in an interconnected world: التّرجمة والثّقافة: العقبات التي تواجه الوِساطة في عالم متّصل - Senoucia, Kihal (Maalim, 2025)
This reflection dives into the heart of the links between translation and culture, intertwining the perspectives of anthropology and sociology to shed light on the current issues of translation studies. A few questions guide our journey: how do the source and target cultures influence the choices of translators? What dilemmas, whether ethical or aesthetic, arise when navigating between different cultural universes? And, above all, can translation really play a role as a bridge, capable of bringing cultures closer together? Translating means embarking on a cultural journey, shaped by the peculiarities of each society. Approaches, techniques, and even the way of interpreting the subtleties of a text vary greatly according to the traditions and expectations specific to each context